Justice in a new world : negotiating legal intelligibility in British, Iberian, and indigenous America - Owensby, Brian Philip, 1959-; Ross, Richard Jeffrey (New York : New York University Press, 2019)
The wide-ranging chapters of this ambitious volume advance our understanding of how Natives and settlers in both the British and Iberian New World empires strained to use the other's law as a political, strategic, and moral resource.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 25, 2019).
Keywords: Indians -- Legal status, laws, etc. -- History; America -- History -- To 1810.; Colonies -- America -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law